The key competemces, and opportunity for the change - Roldán Ruiz, Rosario; Lucena Rubio, Manuel; Torres Caño, Pilar (Avances en Supervisión Educativa, 2009)
Education through key competences is a model that implies to question the whole educational procss, to identify the students as active agents, and to adapt our teaching to their previous knowledge, experience and attitudes. Mainly, this model leads us to think about our role as facilitators of learning and to ackow ledge that our students learn by doing.